Planning and Development of Traditional Tourism in Nablus Governorate - Lubna Mahmoud Muahmmad Ajaj (My University, 2007)
This thesis is concerned with a very important topic and essential in the life of the Palestinian people in general and the community of Nablus in particular. The subject of traditional tourism in Nablus governorate and the means of its development and promotion are discussed in this study, based on reviewing the historical and cultural aspects of Nablus governorate and studying the different conditions and civilizations through successive periods, and their valuable and cultural and tourist remains. The thesis is composed of seven chapters that concentrate on tourism in Palestine in general and in Nablus governorate in particular, through studying and analyzing the current situation of traditional tourism in the governorate; its major components, elements, and potentials as well as the obstacles that face this sector. Moreover, the study proposed a development plan for dealing with the industry of traditional tourism in Nablus governorate. The available data from various related sources in addition to the data collected through the prepared questionnaires, conducted interviews and undertaken field survey are used in analyzing and evaluating the current situation of the traditional tourism in Nablus governorate. The results of the study indicated that the traditional tourism in Nablus governorate was flourished and prosperous during the periods before the year 2000 after which it had a recession and faced various difficulties as a result of the continuous invasions and measures taken by the Israeli occupation, in addition to the lack of adequate infrastructure for traditional tourism. Moreover, the study indicated that traditional tourism in Nablus governorate could witness great development and improvement and could retain its previous prosperity if the required human and financial resources are sustained. The study has recommended getting use of the proposed development plan for the improvement and promotion of traditional tourism in Nablus governorate. Also, it recommended the necessity of cooperation and coordination among all the governmental, nongovernmental and private institutions involved in tourism sector. Finally, the study emphasized the significance of raising the level of public awareness towards tourism, and the importance of providing the governmental assistance for tourism sector in Nablus governorate

تتناول هذه الأطروحة موضوعاً هاماً وحيوياً في حياة المجتمع الفلسطيني بشكل عام والنابلسي بشكل خاص، حيث تُناقش موضوع السياحة التراثية في محافظة نابلس وسبل تنميتها وتطويرها، وتقوم هذه الدراسة على استعراض الأسس التاريخية والحضارية لمحافظة نابلس ومن ثم دراسة الأوضاع التي عاشتها المحافظة عبر العصور المختلفة من حضارات وما تركته هذه الحضارات من معالم وآثار أصبحت تشكل فيما بعد قيمة سياحية وحضارية هامة للمحافظة. تكوَّنت الدراسة من سبعة فصول دراسية ركزت على السياحة بفلسطين بشكل عام ومحافظة نابلس بشكل خاص، وقد تم التطرق خلال الدراسة إلى واقع السياحة التراثية في المحافظة وأهم مكوناتها ومقوماتها وما يعترضها من عقبات ومعيقات ذاتية وموضوعية، وتم تحليل هذه الصعوبات وأسبابها واقترحت الدراسة خطة تنموية من أجل تطوير وتنمية الواقع السياحي في المحافظة. تم الاستعانة بالعديد مصادر المعلومات الصادرة من الجهات ذات العلاقة بالموضوع ودُعمت الدراسة بتحليلات إحصائية من أجل تقييم الواقع السياحي في المحافظة. وأشارت نتائج الدراسة إلى أنَّ السياحة التراثية في محافظة نابلس كانت مزدهرة خلال الفترة التي سبقت عام (2000)، ولكنها شهدت تراجعاً كبيراً نتيجة لظروفٍ عديدة أهمها الاحتلال الإسرائيلي وما نتج عنه من معيقات وإجراءات، إضافة لعدم وجود إلى بنية سليمة ترتكز عليها السياحة التراثية، وأشارت كذلك إلى أن السياحة التراثية في المحافظة يمكن أن تشهد تقدماً وتطوراً كبيرين إذا ما تُوفرت لها الإمكانيات البشرية والمادية المناسبة والظروف الذاتية والموضوعية الملائمة. وأوصت الدراسة إلى الاستعانة بالخطة التنموية المقترحة لتطوير السياحة التراثية في محافظة نابلس، كما وأوصت بضرورة التنسيق والتعاون بين كافة المؤسسات الرسمية والأهلية ومؤسسات القطاع الخاص ذات العلاقة بموضوع السياحة، وأكدت كذلك على أهمية توفير الدعم الحكومي لقطاع السياحة في المحافظة، وأخيراً أوصت الدراسة بالعمل على رفع درجة الوعي بين المواطنين.
تخطيط وتنمية السياحة التراثية في محافظة نابلس